2019
DOI: 10.1016/j.foot.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to self-management: The person-centred diabetes foot behavioural agreement.

Abstract:  98% of diabetes management is self-care  Effective self-foot care can prevent diabetes foot disease  Self-foot care requires functional, interactive and critical health literacy skills  Behavioural agreements delineate, prescribe and support individual responsibilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 47 publications
0
16
0
3
Order By: Relevance
“…Healthcare providers play a unique role in delivering person-centered diabetes self-management education, supporting interventions, and assisting patients to undertake protective self-care behaviors. 58 Other qualitative studies have reported similar findings whereby patients with limited resources were particularly challenged when seeking medical services or obtaining care and support. 59 , 60 Apart from the scarcity of guidance from healthcare providers, the participants also identified the lack of family support as another barrier to diabetes self-management.…”
Section: Discussionmentioning
confidence: 68%
“…Healthcare providers play a unique role in delivering person-centered diabetes self-management education, supporting interventions, and assisting patients to undertake protective self-care behaviors. 58 Other qualitative studies have reported similar findings whereby patients with limited resources were particularly challenged when seeking medical services or obtaining care and support. 59 , 60 Apart from the scarcity of guidance from healthcare providers, the participants also identified the lack of family support as another barrier to diabetes self-management.…”
Section: Discussionmentioning
confidence: 68%
“… 3 More than 95% of diabetes management is self‐care. 4 , 5 Segall and Goldstein described self‐care as comprising behavioural practices such as health maintenance, disease prevention, assessment of symptoms, self‐diagnosis, self‐treatment (non‐medication treatments and self‐medication), self‐referral, consultation with non‐medical (alternative) care practitioners, and the use of specialised medical care. 6 Self‐management has been identified as the cornerstone of diabetes care and an essential part of successfully preventing or delaying diabetes complications.…”
Section: Introductionmentioning
confidence: 99%
“…Perilaku perawatan kaki dapat membantu mengurangi masalah kaki (Lutfi, et al 2014) 49% hingga 85% (Amiga KS et al, 2011). Namun, sulit untuk membuat pasien mempertahankan kebiasaan perawatan kaki setiap hari (Bullen, et al 2019). Sebuah penelitian yang dilakukan peneliti sebelumnya melaporkan bahwa mayoritas pasien dengan diabetes memiliki pengetahuan dan praktik yang buruk terkait dengan perawatan kaki yang tepat (Gatt, et al 2008).…”
Section: Pendahuluanunclassified
“…Para lansia kurang percaya diri dalam melindungi dan memeriksa kaki mereka setiap hari terhadap munculnya gangguan seperti kemerahan, luka, kulit melepuh dan kering. Hambatan melakukan perawatan ini mungkin karena kondisi lansia seperti gangguan penglihatan dan memiliki penyakit medis lainnya yang membatasi kemampuan mereka untuk memeriksa dan melindungi kaki mereka dengan baik (Bullen B, 2019).…”
Section: Pembahasan Tingkat Self-efficacy Kaki Lansia Dengan Diabetesunclassified
See 1 more Smart Citation